Comparative Islamic perspectives in money, monetary policy, and social wellbeing - Choudhury, Masudul Alam (SESRIC, 2018)
Moral and ethical context of money and monetary policy in the creation of a stable and real growth perspective of the economy and wellbeing criterion is formalized. This derivation and casting it into a generalized analytical model is premised on the cardinal Islamic ontological law of unity of knowledge. This spells out the essence of pervasive complementarities between the good things of life as the life-sustaining possibilities of maqasid as-shari’ah, the purpose and objective of shari’ah in term of its direct relationship with the ontological law of Tawhid, oneness of God spelled out in terms of the unity of knowledge and pervasive organic complementarities between the maqasid-goods. The paper thereby makes a distinct difference between the essential reference to Tawhid, thus shari’ah at-Tawhid. This primal conception and methodological worldview is distinctly contrary to the man-made vagaries of what is called ‘shari’ah compliance’. Against such background this paper undertakes a comparative study of the nature of money and monetary policy. This approach leads into the model of money, finance, and real economy model and its various ramifications. An analytical approach is adopted within the comparative perspectives of money and monetary policy for the Islamic case.